2015
DOI: 10.1161/strokeaha.115.008678
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tissue Factor Levels and Risk of Stroke

Abstract: Background and Purpose-Tissue factor (TF) expression is increased in inflammatory atherosclerotic plaques and has been related to their thrombogenicity. Blood-borne TF has been also demonstrated to contribute to thrombogenesis. However, few studies have evaluated the association of circulating levels of TF with stroke. We investigated the association of baseline circulating levels of TF with stroke events occurred in the European Prospective Investigation into Cancer and Nutrition-Italy cohort. Methods-Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Increased expression of TF has previously also been shown to be associated with thrombus formation in patients with ischemic stroke (109,110). The EPICOR study in 2015 revealed that patients with elevated TF doubled the risk of stroke (109). Experimental studies also demonstrated that the inhibition of TNF-α-induced TF significantly reduces atheromatous plaque formation (30).…”
Section: Endothelium-driven Activation Of the Extrinsic Coagulation Systemmentioning
confidence: 98%
“…Increased expression of TF has previously also been shown to be associated with thrombus formation in patients with ischemic stroke (109,110). The EPICOR study in 2015 revealed that patients with elevated TF doubled the risk of stroke (109). Experimental studies also demonstrated that the inhibition of TNF-α-induced TF significantly reduces atheromatous plaque formation (30).…”
Section: Endothelium-driven Activation Of the Extrinsic Coagulation Systemmentioning
confidence: 98%
“…19 This type of feed-forward prothrombotic signaling cascade helps to coat infected cells with fibrin, potentially shielding them from immune cell targeting. Importantly, individuals with higher levels of circulating tissue factor harbor a 2-fold increased risk of stroke 20 that may place them in a baseline prothrombotic state and therefore more susceptible to virally-mediated activation of coagulation. Whether similar direct molecular interactions between viral proteins and proteins in the coagulation cascade occurs in Sars-CoV-2 infection is largely unknown but given the high rate of prothrombotic complications including stroke seen in severe COVID-19 infections, this molecular hijacking deserves further study.…”
Section: Sars-cov-2 Mediated Systemic Hypercoagulability As a Driver mentioning
confidence: 99%
“…Atherosclerotic cardiovascular and cerebrovascular diseases are still major causes of morbidity and mortality worldwide. [13][14][15][16][17] Tissue factor, which is present as Factor III in the clotting pathway and also known as "CD 142" and "thromboplastin", is a transmembrane protein which enables thrombin formation and is multifunctional. Parallel to today's technology, there are many studies aiming to better know the structure of tissue factor, while reporting that this protein is not only effective in the clotting system, but also in inflammation and cancer formation.…”
Section: -11mentioning
confidence: 99%